1991
DOI: 10.1128/jcm.29.9.1955-1958.1991
|View full text |Cite
|
Sign up to set email alerts
|

Rapid presumptive identification of black-pigmented gram-negative anaerobic bacteria by using 4-methylumbelliferone derivatives

Abstract: A rapid method for presumptive identification of black-pigmented gram-negative anaerobic rods was developed. Using filter paper spot tests for indole production, sialidase, ot-glucosidase, I-glucosidase, ft-fucosidase, and trypsinlike enzyme activities, 100% of Porphyromonas gingivalis, PrevoteUa intermedia, and Bacteroides levii and 89% of Prevotella corporis isolates were correctly identified to the species level. Porphyromonas asaccharolytica and Porphyromonas endodontalis could not be differentiated from e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0
1

Year Published

1993
1993
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(19 citation statements)
references
References 20 publications
2
16
0
1
Order By: Relevance
“…MLEE provides a definitive distinction between P. intermedia and P. nigrescens [1] but MDH and GDH enzymes from the vaginal isolates did not have migration rates which corresponded to either species. The reactivity of the three strains with the mAbs used here also indicates that they are not P. intermedia or P. nigrescens, and together these results strengthen the proposal made by Moncla et al [16] that they represent a previously undescribed species which is nonetheless biochemically similar to P. intermedia and P. nigrescens. Further studies of these and other organisms identified as P. intermedia, and isolated from non-oral sites, are in progress.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…MLEE provides a definitive distinction between P. intermedia and P. nigrescens [1] but MDH and GDH enzymes from the vaginal isolates did not have migration rates which corresponded to either species. The reactivity of the three strains with the mAbs used here also indicates that they are not P. intermedia or P. nigrescens, and together these results strengthen the proposal made by Moncla et al [16] that they represent a previously undescribed species which is nonetheless biochemically similar to P. intermedia and P. nigrescens. Further studies of these and other organisms identified as P. intermedia, and isolated from non-oral sites, are in progress.…”
Section: Discussionsupporting
confidence: 88%
“…The vaginal isolates used in this study were shown previously to be atypical in that they failed to react with RNA probes prepared against nucleic acid of strains of genotypes I or II of P. interrnedia (i.e.P. intermedia and P. nigrescens), and they were a-fucosidase negative [16]. MLEE provides a definitive distinction between P. intermedia and P. nigrescens [1] but MDH and GDH enzymes from the vaginal isolates did not have migration rates which corresponded to either species.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The chnical isolates were designated according to patient number, site number and isolate number as follows: P 4.3.5, P 6. All isolates were identified according to the methods of Moncla et al (12). Five commonly used laboratory isolates (W50, W83, ATCC 49417, Pg22 KNG.12, PgIET3.10) were also included in the study.…”
Section: Materials and Methods Bacterial Strains And Culture Conditionsmentioning
confidence: 99%
“…All P. gingivalis strains were originally human isolates donated to the laboratory. Species identity was confirmed via reactivity with a range of fluorescent substrates for hydrolytic enzymes basically as described by Moncla et al [20] except a 96-well microtitire plate was used for assays. Bacteria were grown in brain-heart infusion broth (Oxoid, Basingstoke, UK) supplemented with 5 mg/1 hemin.…”
Section: Bacterial Strains and Growth Conditionsmentioning
confidence: 99%